Aggressive delinquency among north American indigenous adolescents: Trajectories and predictors. Issue 3 (9th September 2015) - Sittner, Kelley J.; Hautala, Dane
Abstract : Aggressive delinquency is a salient social problem for many North American Indigenous (American Indian, Canadian First Nations) communities, and can have deleterious consequences later in life. Yet there is a paucity of research on Indigenous delinquency. Group‐based trajectory modeling is used to prospectively examine trajectories of aggressive delinquency over the course of adolescence using data from 646 Indigenous adolescents from a single culture, spanning the ages of 10–19. Five aggression trajectory groups were identified, characterized by different levels and ages of onset and desistence: non‐offenders (22.1%), moderate desistors (19.9%), adolescent‐limited offenders (22.2%), high desistors (16.7%), and chronic offenders (19.2%). Using the social development model of antisocial behavior, we selected relevant risk and protective factors predicted to discriminate among those most and least likely to engage in more aggressive behavior. Higher levels of risk (i.e., parent rejection, delinquent peers, substance use, and early dating) in early adolescence were associated with being in the two groups with the highest levels of aggressive delinquency. Positive school adjustment, the only significant protective factor, was associated with being in the lowest aggression trajectory groups. The results provide important information that could be used in developing prevention and intervention programs, particularly regarding vulnerable ages as well as malleable risk factors. Identifying those youth most at risk of engaging in higher levels of aggression may be key to preventing delinquency and reducing the over‐representation of Indigenous youth in the justice system. Aggr. Behav. 42:274–286, 2016. © 2015 Wiley Periodicals, Inc.